The identity of Israel's God in Christian Scripture - Collett, Don C., 1963-; Elliott, M. W. (Mark W.); Gignilliat, Mark S.; Radner, Ephraim, 1956-; Seitz, Christopher R. (Atlanta SBL Press, 2020)
"Biblical scholars and theologians approach the question of who Israel's God is for Christians in this interdisciplinary collection of essays. Essays on both Testaments focus on figural exegesis, critical exegesis, and the value of diachronic understandings of the Old Testament's compositional history for the sake of a richer synchronic reading. Each contribution reflects upon the implkications of biblical theology and theological exegesis for interpretation of the Old and a New Testament bound together in a single scriptural legacy."--
"Essays in honor of Christopher R. Seitz"-- Preliminary pages.
Includes bibliographical references (pages 411-452) and indexes.
In English, with one contribution in German.
Keywords: Bible -- Criticism, interpretation, etc; God -- Biblical teaching; God (Christianity); God (Christianity); Criticism, interpretation, etc; Festschriften